Study on excimer laser irradiation for controlled dehydrogenation and crystallization of boron doped hydrogenated amorphous/nanocrystalline silicon multilayers - Gontad, F. (2013)
We report on the excimer laser annealing (ELA) induced temperature gradients, allowing controlled crystal-lization and dehydrogenation of boron-doped a-Si:H/nc-Si:H multilayers. Depth of the dehydrogenation and crystallization process has been studied numerically and experimentally, showing that temperatures below the monohydride decomposition can be used and that signiﬁcant changes of the doping proﬁle can be avoided. Calculation of temperature proﬁles has been achieved through numerical modeling of the heat conduction differential equation. Increase in the amount of nano-crystals, but not in their size, has been demonstrated by Raman spectroscopy. Effective dehydrogenation and shape of the boron proﬁle have been studied by time of ﬂight secondary ion mass spectroscopy. The relatively low temperature threshold for dehydrogenation, below the monohydride decomposition temperature, has been attributed to both, the large hydrogen content of the original ﬁlms and the partial crystallization during the ELA process. The results of this study show that UV-laser irradiation is an effective tool to improve crystallinity and dopant activation in p+-nc-Si:H ﬁlms without damaging the substrate.